Empowering employees with spiritual intelligence for higher quality food-hygiene practices and food service performance - Anita, Abdul Rani; Mazni, Ismail; Rosita, Husain; Airin, AbdulGhani (2018)
Empowering employees’ spiritual intelligence (SQ) is about bringing back the soul of the hospitality business. This study aims to identify factors that affect a food handler’s’ SQ and also to discover SQ’s potential role in mediating food-hygiene practices and foodservice performance. The results show that demographic factors significantly affect SQ level. Food-hygiene practices and food service performance were fully mediated by SQ, thus supporting the food handlers’ thoughts of self-development and success at work. It is proposed that the positive outcomes from the large and varied datasets of the model can be generalized to the routine practices and performance of other institutions.